Qu'est-ce que le design? (aujourd'hui). - Morel, Frédéric; Bousteau, Fabrice (Paris : Beaux Arts S.A.S., 2004)
Arad, Ron ; S. & T. Azumi ; Béhar, Yves ; Bergne, Sebastian ; Bey, Jurgen ; Biecher, Christian ; Boontje, Tord ; R. & E. Bouroullec ; Branzi, Andrea ; Brizio, Fernando ; H. & F. Campana ; Charpin, Pierre ; Cissé, Nicolas ; Crasset, Matali ; De Lucchi, Michele ; Dixon, Tom ; Fukasawa, Naoto ; Ghion, Christian ; Grawunder, Johanna ; Grcic, Konstantin ; Guixé, Marti ; Ive, Jonathan ; Jongerius, Hella ; Jouin, Patrick ; Magistretti, Vico ; Marchand, Christophe ; Mari, Enzo ; Maurer, Ingo ; Mendini, Alessandro ; Mir, Ana ; Morrison, Jasper ; Newson, Marc ; Novembre, Fabio ; Ito, Ora ; Paulin, Pierre ; Pesce, Gaetano ; Pillet, Christophe ; Putman, Andrée ; Radi Designers ; Rashid, Karim ; Ruiz de Azua, Martin ; Salli, Timo ; Sandell, Thomas ; Seymour, Jerszy ; Sottsass, Ettore ; Sousa Santos, Marco ; Starck, Philippe ; Suppanen, Ilkka ; Szekely, Martin ; Wanders, Marcel
Schenking Flanders DC
boek